The Free State’s approach to implementing the Comprehensive Plan: notes by a participant outsider - Dingie van Rensburg (Acta Academica, 2006)
This study reviews the first two years of implementation of the Comprehensive Plan in the Free State, within the national framework and amid external influences. The features and principles of the province’s approach are analysed, in particular the phased, multimodel, PHC-centred nature and its emphasis on partnerships and inclusiveness. As implementation progresses, constraints and deficiencies are seen to emerge: a lack of leadership and support, a flawed national-provincial relationship, a lack of comprehensiveness, programme verticalisation, drug insecurity, chronic  indecision and lack of action, a fixation on operational issues with concomitant neglect of strategic matters, and breakdowns in communication and co-ordination. Despite notable progress in implementation, it  is necessary to rethink and redesign aspects of the approach. By identifying the major lessons to be learnt from the Free State’s experience, this study attempts to inform such rethinking and redesigning, as well as highlighting lessons for application elsewhere.